Effects of Trade, Environment Quality and Human Capital on Industrial Sector Output in Developing Countries: A Panel Data Analysis - Nasim, Ismat; Chaudhry, Imran Sharif; Bashir, Furrukh (iRASD Journal of Economics, 2022)
The study is conducted to explore the effectiveness of various variables i.e. Trade, Environmental Quality and Human Capital on Industrial Sector Output by taking data of 63 developing economies, Panel Unit root and Panel ARDL approaches are applied for empirical results. The supporting variable are selected from theoretical support like Labor, Capital, Broad Money, GDP deflator and human capital. The study explores that Money Supply, Human Capital, Government Expenditure and Capital Stock are increasing industrial sector output, but it is reduced by Carbon Dioxide Emission, Trade Openness, Labor Force and Price Level.